The State-of-the-Art of Gene Editing and its Application to Viral Infections and Diseases Including COVID-19 - Hawsawi, Yousef M.; Shams, Anwar; Theyab, Abdulrahman; Siddiqui, Jumana; Barnawee, Mawada; Abdali, Wed A.; Marghalani, Nada A.; Alshelali, Nada H.; Al-Sayed, Rawan; Alzahrani, Othman; Alqahtani, Alanoud; Alsulaiman, Abdulrahman M. (Frontiers in Cellular and Infection Microbiology, 2022)
Gene therapy delivers a promising hope to cure many diseases and defects. The discovery of gene-editing technology fueled the world with valuable tools that have been employed in various domains of science, medicine, and biotechnology. Multiple means of gene editing have been established, including CRISPR/Cas, ZFNs, and TALENs. These strategies are believed to help understand the biological mechanisms of disease progression. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been designated the causative virus for coronavirus disease 2019 (COVID-19) that emerged at the end of 2019. This viral infection is a highly pathogenic and transmissible disease that caused a public health pandemic. As gene editing tools have shown great success in multiple scientific and medical areas, they could eventually contribute to discovering novel therapeutic and diagnostic strategies to battle the COVID-19 pandemic disease. This review aims to briefly highlight the history and some of the recent advancements of gene editing technologies. After that, we will describe various biological features of the CRISPR-Cas9 system and its diverse implications in treating different infectious diseases, both viral and non-viral. Finally, we will present current and future advancements in combating COVID-19 with a potential contribution of the CRISPR system as an antiviral modality in this battle.